User Interface Design and UML-Based Modeling for an Internship Monitoring and Evaluation Information System - Nurul Zafirah; Ikhsan Pratama; Samsudin (Journal of Information Systems and Technology Research, 2026)
Conventional internship monitoring workflows frequently suffered from critical inefficiencies, including data fragmentation, delayed reporting, and subjective performance evaluations. Furthermore, existing literature on system design often prioritized backend logical structures while neglecting frontend visual usability, resulting in functional but difficult-to-use applications. This study aimed to address these specific gaps by designing a comprehensive internship monitoring and evaluation system that explicitly integrated strict Unified Modeling Language architecture with high-fidelity user interface design at the conceptual level. The methodology utilized a qualitative descriptive approach, employing specific structural diagrams including use case, activity, and sequence diagrams to enforce role-based access control and user-centered design principles. The results demonstrated that the proposed blueprint successfully ensured data integrity and atomicity. Validated through black box testing, the conceptual models were confirmed to be translated into a functional design without logical errors, enabling real-time activity tracking and objective assessment. This study contributed to information system design research by bridging strict data security standards with minimalist usability heuristics, providing a matured visual and structural foundation. The findings offered a concrete basis for future implementation and empirical validation using user acceptance testing in operational environments.